Ancient vicariance driven by geology reinforced by adaptive divergence in a southern beech tree: contributions from Geogenomics - Fasanella, Mariana (2022)
Se adjunta la base de datos en crudo de los 2943 SNPs de 113 individuos de Nothofagus dombeyi utilizada en el artículo: Ancient vicariance driven by geology reinforced by adaptive divergence in a southern beech tree: contributions from Geogenomics